Secondary multicystic changes in the contralateral lung associated with Congenital Diaphragmatic Hernia - A. Wise, MD; M. Evans, MD (Elsevier, 2018)
In this report we present a case of extensive cystic changes of the lung that developed postnatally in an infant with right Congenital Diaphragmatic Hernia. The cystic changes occurred on contralateral side, in the setting of relatively low mean airway pressures. With gentle ventilatory techniques, Heliox, and intentional collapse of the affected lung, the cysts gradually resolved. Keywords: Congenital Diaphragmatic Hernia, Secondary cystic lung changes, Neonate